Media Sosial dan Kesehatan Mental: Tinjauan Teologi Siber Dalam Konteks Orang Muda Katolik Keuskupan Denpasar - Ardhiatama, William Fortunatus Dani (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2025)
The focus of this study is to examine the impact of social media on the mental health of Catholic Youth in the Diocese of Denpasar from the perspective of cyber theology as proposed by Antonio Spadaro. Social media has now become an inseparable part of young people's daily lives. Its presence significantly influences human life today, particularly the youth. Therefore, it is crucial to observe and respond wisely to the presence of social media along with its effects. This research employs a qualitative research method, using in-depth interviews with respondents representing the Catholic Youth of the Diocese of Denpasar. The collected data is then analyzed through the lens of cyber theology as conceptualized by Antonio Spadaro. The findings reveal that while social media can broaden relationships, increase access to information, and serve as a medium for deepening faith, it can also affect the mental health of young people if not used wisely and responsibly. Efforts to address the potential negative impacts of social media must be undertaken earnestly. The Church is also called to be actively involved in this context through its pastoral mission. It is invited to be a welcoming home and an engaged community to support young people in navigating the challenges posed by social media.